Rho-Meson propagator at two-loop order in the Kroll-Lee-Zumino quantum field theory - Lushozi, Mawande (Department of Physics, 2017)
The Kroll-Lee-Zumino theory, an Abelian renormalizable quantum field theory of charged pions and a neutral ρ meson, provides a framework to compute corrections to the tree-level Vector-Meson-Dominance model. Despite a large ρππ coupling (gρππ ≈ 5), the loop suppresion factor of 1=(4π)² helps give reasonably small NLO (one-loop) corrections. When it comes to describing hadronic physics, one might say, these one-loop results achieve moderate to excellent success. Where the one-loop results show less than impressive agreement with experiment, it seems plausible that the NNLO (two-loop) corrections would remedy the situation. In this thesis the two-loop contribution to the ρ⁰ meson is calculated. It turns out to be larger than the one-loop result and so one must conclude that perturbation theory breaks down at this level.